Cycle Time Minimization During Renewable Methane Production from H2O2 Enhanced Anaerobic Co-Digestion of Petrochemical Wastewater in Continuous Stirred Tank Reactor - Nurul Islam Siddique, Md.; Zularisam, A.W. (Asian Journal of Chemistry, 2012)
The latent of per-oxidation pretreatment to petrochemical wastewater prior to anaerobic co-digestion process was explored in continuous stirred tank reactor continually with dairy cattle and beef cattle manure. Hydrogen peroxide oxidation, elevated biodegradability index (BOD/COD) up to 35 %. While continuous stirred tank reactor operated with non-oxidation by hydrogen peroxide petrochemical waste water system was failed at organic loading of 6.5-12.99 kg COD/m3/d due to vigorous volatile fatty acid accumulation. Inversely, oxidation by hydrogen peroxide petrochemical waste water rendered sustainable superior total COD removal at 6.03-11.7 kg COD/m3/d organic loading with durable process stability at co-digestion period. As methane production is considered to be inhibited due to volatile fatty acid accumulation leading to instability of reactor operation during anaerobic digestion, co-digestion of oxidation by hydrogen peroxide pretreated petrochemical waste water resulted in exaggerated methane yield, followed by 98 ± 0.5 %, 95 ± 0.05 % and79 ± 0.06 % COD reduction at 9, 6 and 4 days hydraulic retention time. The concrete data revealed that prolonged hydraulic retention time and abridged cycle time caused continuous stirred tank reactor aggrandized total COD removal efficiency and methane yield.